2010
DOI: 10.1042/bst0381581
|View full text |Cite
|
Sign up to set email alerts
|

The role of IRES trans-acting factors in regulating translation initiation

Abstract: The majority of mRNAs in eukaryotic cells are translated via a method that is dependent upon the recognition of, and binding to, the methylguanosine cap at the 5' end of the mRNA, by a set of protein factors termed eIFs (eukaryotic initiation factors). However, many of the eIFs involved in this process are modified and become less active under a number of pathophysiological stress conditions, including amino acid starvation, heat shock, hypoxia and apoptosis. During these conditions, the continued synthesis of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
102
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 113 publications
(105 citation statements)
references
References 60 publications
3
102
0
Order By: Relevance
“…This could indicate that the putative IRES motif spans over a larger part of the PTCH1b 5'UTR, potentially even extending to the coding region, or that contiguous part(s) of PTCH1b 5'UTR harbor binding sites for IRES trans-acting factors (ITAFs), required for proper folding and function of the IRES motif itself. 62 The results achieved with remodeled pRuF-based PTCH1b 5'UTR plasmids were also proven to be due to the translational and not transcriptional processes. Considering all these results, our study has presented strong evidences that PTCH1b 5'UTR contains an internal ribosome entry site, and is thus potentially capable to initiate PTC1-L translation in cap-independent manner.…”
Section: Discussionmentioning
confidence: 97%
“…This could indicate that the putative IRES motif spans over a larger part of the PTCH1b 5'UTR, potentially even extending to the coding region, or that contiguous part(s) of PTCH1b 5'UTR harbor binding sites for IRES trans-acting factors (ITAFs), required for proper folding and function of the IRES motif itself. 62 The results achieved with remodeled pRuF-based PTCH1b 5'UTR plasmids were also proven to be due to the translational and not transcriptional processes. Considering all these results, our study has presented strong evidences that PTCH1b 5'UTR contains an internal ribosome entry site, and is thus potentially capable to initiate PTC1-L translation in cap-independent manner.…”
Section: Discussionmentioning
confidence: 97%
“…Initiation protein factors are released from the 48S initiation complex upon GTP hydrolysis by eIF2 , and the 60S ribosome subunit joins the 40S ribosome subunit to form 80S initiation complex in a process that is aided by eIF5B. Elongation of polypeptide chain synthesis commences following 80S initiation complex formation at AUG (for detail reviews see Gebauer & Hentze, 2004;Holcik & Sonenberg, 2005;Graber & Holcik, 2007;King et al, 2010) (Figure 1). …”
Section: Introductionmentioning
confidence: 99%
“…During physiological or pathophysiological stress conditions the cap-dependent translation initiation is compromised either due to the proteolytic cleavage of initiation factors or changes in the phosphorylation status of the initiation factors and their binding partners (reviewed in King et al, 2010). A class of mRNAs harbouring Internal Ribosome Entry Site (IRES) can bypass the global attenuation of protein translation.…”
Section: Introductionmentioning
confidence: 99%
“…94,[122][123][124][125] Using pull-down experiments Vallejos et al 41 identified a series of proteins found in G2/M HeLa extracts that interact with the viral 5 0 UTR. However, these findings are very preliminary as their role in translation initiation was not evaluated in a functional assay.…”
mentioning
confidence: 99%
“…However, under various cellular and environmental stresses, global protein synthesis declines and expression of diverse stressresponsive factors driven by IRESes are preferentially upregulated. [122][123][124]131 As such, cellular mRNAs can switch from capdependent to cap-independent translation as an adaptive response of stress resistance [122][123][124]131 ; this may also be the case for translation initiation from the HIV-1 mRNA.…”
mentioning
confidence: 99%